Efficient biosynthesis of serotonin and melatonin through combinatorial metabolic engineering in Escherichia coli - Dejun Wan; Baodong Hu; Jingwen Zhou; Jianghua Li; Jian Chen; Guocheng Du; Xinrui Zhao (Food Bioscience, 2026)

Rapid retreat of the East Asian summer monsoon at the end of the Holocene humid period accelerated the transition from broadleaf to pine forest landscapes in northern China - Linjing Liu; Xin Mao; Lei Song; Xingqi Liu; Dejun Wan; Gaolei Jiang; Jingsong Yang; Hongmei Zhao; Chengmin Wang; Hua Zhao; Rong Ma (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Variable erosion depth in the Chinese Loess Plateau driven by human activities: Evidence from lacustrine uranium comminution ages - Run Zhang; Laifeng Li; David William Hedding; Dejun Wan (Quaternary Science Reviews, 2026)

Ecological responses of the largest lake-wetland system (North China Plain) to hydrological regulation and cultural eutrophication over the past 70 years - Longjuan Cheng; John P. Smol; Qi Lin; Chaoran Wei; Shuyi Yang; Dejun Wan; Qingfeng Jiang; Dongliang Ning; Bin Xue (Anthropocene, 2026)

Fungal denitrification dominates soil N2O emissions after vegetation restoration in the karst region - Huifang Xu; Chengyi Lao; Teng Yu; Ziwei Wan; Pengpeng Duan; Kongcao Xiao; Dejun Li (Soil Ecology Letters, 2026)

Enhancing SUHI monitoring in mountainous cities: A comparative study of Chongqing and Chengdu, China - Dejun Zhang; Shiqi Yang; Hao Zhu; Qinyu Ye; Zeneng He; Wan Zhou; Yuyu Zhou (Urban Climate, 2025)

Late Holocene fluctuations in the Indian Summer Monsoon forced centennial-scale patterns of hydrogeomorphic evolution in the Yamdrok Yumtso Basin of the southern Tibetan Plateau - Zemin Zhi; Xiaqing Wang; Fenggui Liu; Dejun Wan; Qiang Zhou; Feiya Lv; Pengjia Zhang; Kehan Zhou; Jianhua He (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Characterization of Metal Contamination in a Lake of Southeast Hubei: Insights Into Dissolved and Particulate Fractions and Associated Health Risks - Zhiqi Song; Zipeng Zeng; Changlin Zhan; Shan Liu; Min Guo; Ziguo Liu; Fei Zhang; Dejun Wan (Water, Air, & Soil Pollution, 2025)

CsAHL20 negatively regulates epi-catechins biosynthesis under drought stress in Camellia sinensis - Yu Chen; Mingyuan Luo; Ping Li; Qi Zhao; Luo Chao; Yujie Jiao; Shiyu Tian; Xingyu Tian; Shenyuan Ye; Zhenkedai Yuan; Yilan Hu; Yongqing Bai; et al. (Plant Science, 2025)

Life cycle assessment and optimization scenarios of sofas: a case study in China - Ruiying Wan; Xianqing Xiong; Sijie Fu; Dejun Xiong; Xiutong Xu (The International Journal of Life Cycle Assessment, 2025)

The long-term environmental evolution of an urban lake in the highly developed Yangtze River Delta - Zhenglan Fu; Longjuan Cheng; Qingfeng Jiang; Jiali Zhang; Xinyue Chen; Shuyi Yang; Xinyuan Gao; Xiang Kuai; Dejun Wan; Dongliang Ning; Bin Xue (Journal of Geographical Sciences, 2025)

Ecosystem Shifts and Cladocera Responses in a Freshwater Lake in Semi‐Arid Regions: The Successional Synergistic Effects of Natural and Human Factors in the Past 170 Years - Longjuan Cheng; Bin Xue; Jinliang Liu; Xiangzhen Kong; Can Zhang; Dejun Wan; Qingfeng Jiang; Dongliang Ning; Wenxiu Zheng (Journal of Biogeography, 2025)
Aim Freshwater lake ecosystems in semi‐arid regions are highly fragile and complex. However, the driving forces behind changes in temperate lake ecosystems at a regional scale in China remain largely unclear, primarily due to the lack of multidecadal to centennial regional studies. This study focuses on Hulun Lake, the largest freshwater lake in northern China's semi‐arid region, with the aim of elucidating the characteristics and driving mechanisms of freshwater lake ecosystems in such areas. Location Hulun Lake, the largest freshwater lake in northern China's semi‐arid region (48.55° ~ 49.33° N, 116.97° ~ 117.81° E). Time Period From the 1840s to 2010s AD. Major Taxa Studies Zooplankton Cladocera. Methods High‐resolution multiproxy palaeoecological data (including biological and geochemical indices), human activities parameters and observational datasets from the lake basin are used to explore ecosystem shifts and Cladocera responses in Hulun Lake, located in a semi‐arid region, over the past 170 years. The hypothesis that changes in the zooplankton Cladocera community composition within the ecosystem are driven by synergistic interactions among multiple factors was tested using effective approaches based on generalised additive models (GAM) and redundancy analysis (RDA). Results The results indicate that both internal factors (such as lake sedimentary environment, fish catches, lake water level, organic matter and nutrients) within the lake and external factors (including population, urbanisation rate and livestock husbandry) in the surrounding basin have been key drivers influencing the structure of Cladocera in Hulun Lake over the past 170 years. The originally predominant littoral Cladocera species ( Chydorus sphaericus . sl.) were replaced by planktonic (Bosminidae) since the 1980s accompanied by a decline in diversity, which corresponds with the process of eutrophication and pollution in the lake. Main Conclusions The dynamics of the Cladocera assemblages indicate that the lake ecosystem is vulnerable to further imbalance since the 2000s due to the ongoing synergistic effects of declining fishery catches, increasing livestock numbers, rising populations, urbanisation rates and declining water levels in semi‐arid regions.

Reliability assessment of using different heavy metals in remote sedimentary records to reconstruct historical pollution - Jiapeng Gao; Ruiting Song; Xinrui Wang; Kexin Wan; Jianle Zhang; Guanqi Shan; Dejun Wan; Shaogang Wang (Environmental Pollution, 2025)

Vegetation, temperature, and Indian Summer Monsoon evolution over the past 4400 years revealed by a pollen record from Drigo Co on the southern Qinghai-Tibet Plateau - Feiya Lv; Xiaqing Wang; Fenggui Liu; Dejun Wan; Kehan Zhou; Pengjia Zhang; Yumei Peng; Shengrui Zhang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Decadal trends of black carbon and heavy metal accumulation in a lake sediment core from central China: A historical perspective - Changlin Zhan; Dejun Wan; Yongming Han; Jiaquan Zhang; Shan Liu; Hongxia Liu; Tianpeng Hu; Wensheng Xiao; Junji Cao; Dong Li (CATENA, 2024)

Yr29 combined with QYr.nwafu-4BL.3 confers durable resistance to stripe rust in wheat cultivar Jing 411 - Mingjie Xiang; Bo Tian; Jianghao Cao; Shengjie Liu; Caie Zhou; Xiaoting Wang; Yibo Zhang; Jiale Li; Xunying Yuan; Jufen Wan; Rui Yu; Weijun Zheng; et al. (Theoretical and Applied Genetics, 2024)

Sources and factors influencing lacustrine carbon burial over the last century: case study of Yinjia Lake, central China - Changlin Zhan; Dejun Wan; Yongming Han; Shan Liu; Jiaquan Zhang; Hongxia Liu; Tianpeng Hu; Wensheng Xiao; Junji Cao (Journal of Paleolimnology, 2024)

Prevalence and characterization of aminoglycoside resistance gene aph(2”)-If-carrying Campylobacter jejuni - Jin Kang; Cheng Zhang; Shuigen Wan; Wenjun Li; Wenbo Zhao; Longyu Li; Yanhong Shang; Xiang-Dang Du; Dejun Liu; Hong Yao (International Journal of Food Microbiology, 2024)

Millennial to orbital scale Indian summer monsoon evolution inferred from grain size end-members in Tengchongbeihai wetland, southwestern China - Dongliang Ning; Xiayun Xiao; Suqin Tang; Yuchen Xu; Xiang Kuai; Ying Ge; Jianan Zheng; Longjuan Cheng; Dejun Wan; Qingfeng Jiang; Yanling Li (Quaternary Science Reviews, 2024)

Luteolin inhibits the JAK/STAT pathway to alleviate auditory cell apoptosis of acquired sensorineural hearing loss based on network pharmacology, molecular docking, molecular dynamics simulation, and experiments in vitro - Fang Guo; Yingyuan Guo; Dejun Zhang; Zeming Fu; Shuang Han; Yining Wan; Guofang Guan (Toxicology and Applied Pharmacology, 2024)

Sediment records of black carbon variations over the last two centuries in North China - Dejun Wan; Yongming Han; Lei Song; Dongliang Ning; Qingfeng Jiang (Science of The Total Environment, 2023)

Two-century sediment records of atmospheric mercury variations in North China and their relations with regional and global emissions - Dejun Wan; Handong Yang; Zhangdong Jin; Lei Song; Dongliang Ning; Longjuan Cheng; Qingfeng Jiang (Environmental Science and Pollution Research, 2023)

A multi-proxy record of climate variations over the last millennium from Kulun-nuur Lake sediments, Inner Mongolia, north-central China - Xin Mao; Dejun Wan; Lei Song; Jingsong Yang; Linjing Liu; Gaolei Jiang; Junfeng Li; Xingqi Liu (Journal of Paleolimnology, 2021)

A ~ 230-year dust storm record from China’s Lake Gonghai on the northeast Loess Plateau - Lishuai Xu; Dejun Wan; Yonghong Duan; Yongchong Lin; Guijin Mu; Zhilei Zhen; Yongsheng Yang (Arabian Journal of Geosciences, 2021)

Oasis microclimate effect on the dust deposition in Cele Oasis at southern Tarim Basin, China - Lishuai Xu; Guijin Mu; Xiao Ren; Dejun Wan; Junxia He; Yongchong Lin (Arabian Journal of Geosciences, 2016)

Spatial uniformity in the mineralogical and geochemical compositions of surface sediments in Lake Qinghai and their controlling factors - Liu-Mei Chen; Zhangdong Jin; Dejun Wan; Fei Zhang (Limnology, 2015)

Further quantifying the fluxes and contributions of sources to modern sediment in Lake Qinghai, NE Tibetan Plateau - Dejun Wan; Zhangdong Jin; Fei Zhang; Hongyun Chen; Liumei Chen; Lei Song; Chao Song (Limnology, 2015)

In vitro comparison of the hemocompatibility of diamond-like carbon and carbon nitride coatings with different atomic percentages of N - MengLi Zhao; DeJun Li; YiTeng Zhang; MeiXian Guo; XiangYun Deng; HanQing Gu; RongXin Wan (Science China Life Sciences, 2012)